A Glucuronidation Pathway of Capecitabine Occurs in Rats but Not in Mice and Humans - Desmoulin, F.; Claparols, C.; Bon, D.; Larrieu, G.; Martino, R.; Malet-Martino, M. (Drug Metabolism Letters, 2007)
Glucuronidation of 5'-DFCR, a metabolite of capecitabine, was confirmed in experimental models from rats whereas 5'-DFCR glucuronide was detected neither in bile or liver from mice nor in livermicrosomes from human. Metabolic interactions at the level of the glucuronidation pathway between CAP and other drugs are unlikely in patients.
Keywords: mice